Analisis Film Bayi Ajaib Karya Alim Sudio(Semiotika Charles Sanders Peirce): Analysis of Alim Sudio's Bayi Ajaib Movie (Charles Sanders Peirce Semiotics) - Maharani, Binta; Sumarti, Endang; Rachman, Anita Kurnia (Wacana : Jurnal Bahasa, Seni, dan Pengajaran, 2024)
This research explored the semiotic representation of Javanese mysticism in Alim Sudio's film "Bayi Ajaib," employing Charles Sanders Peirce's semiotic framework to analyze the use of icons, indexes, and symbols. The study, focusing on the film's portrayal of supernatural beliefs prevalent within Javanese culture, utilized verbal and non-verbal data, including dialogues and visual elements. Data collection involved film observation, transcript creation, and coding of semiotic elements. Analysis, conducted using the Miles and Huberman model, revealed distinct applications of Peirce's categories. Icons were observed in sentences expressing future imagination and visuals mirroring real-world forms. Indexes were employed to generate tension and emotional engagement, contributing to the film's narrative. Symbols, such as the ayam cemani and sajen, were utilized to represent agreed-upon cultural elements within Javanese tradition. The study provides insights into how semiotics are utilized to convey cultural beliefs and mystical themes within a cinematic context, highlighting the film's reflection of Javanese society's enduring fascination with the supernatural.